Preserving Electronic Records in Ghana: Implications for National Heritage - Akussah, Harry (Ghana Library Journal, 2002)
With the revolutionary global shift from print to electronic media as means of documentation and communication, the landscape of managing records is changing fast. In Africa, the public sector is more hit as a result of the lack of resources, legislative framework, infrastructure and in stitutional capacity. The article discusses the preservation of electronic documents in the public sector of Gitana and the implications for national heritage. It highlights key issues including, legislative reviews, technological support, staff reengineermg and capacity building and the active involvement of records and archives managers in the "conception" stage of electronic documents.